(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
This article presents a set of standardised corpora of poetry comprising over 330,000 poems in ten languages (Czech, English, French, German, Hungarian, Italian, Portuguese, Russian, Slovenian, and Spanish). Each corpus has been deduplicated, enriched with Universal Dependencies, provided with additional metadata, and converted into a unified json structure.